THE ROLE OF COGNITIVE THEORY IN TRANSLATION OF METAPHORICAL SCIENTIFIC TERMS - Naciscione, Anita (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
My aim is to have a closer look at the benefits of a cognitive linguistic approach to scientific discourse, its metaphorical terms and their translation. This area of research has emerged over recent decades. What role do metaphors play in science and terminology? Why do metaphors appear in scientific terms? The reasons are cognitive. My approach is based on the findings of cognitive linguistics about the significance of metaphor in thought and language, and my own translation and interpreting experience. Metaphor has been recognised as a basic technique of reasoning that is also manifest in terminology, which is an important area of meaning construction. Theoretical conclusions are drawn, applying the tenets of Cognitive Linguistics, translation theory, semantic and stylistic analyses of the empirical material, which I have chosen from my own archive of metaphorical terminology and my glossaries of simultaneous conference interpreting. Translation of metaphorical scientific terminology falls within the realm of Applied Linguistics, which is an interdisciplinary field, drawing on a number of disciplines apart from linguistics. Applied Linguistics calls for a theoretical understanding of language in use to meet user needs. It is not an end in itself as it has practical worth and application.